The physical chemistry of materials : energy and environmental applications - Roque-Malherbe, Rolando M. A. (CRC Press, 2010)
In recent years, the area dealing with the physical chemistry of materials has become an emerging discipline in materials science that emphasizes the study of materials for chemical, sustainable energy, and pollution abatement applications. Written by an active researcher in this field, Physical Chemistry of Materials: Energy and Environmental Applications presents methods for synthesizing and characterizing adsorbents, ion exchangers, ionic conductors, heterogeneous catalysts, and permeable porous and dense materials. It also discusses their properties and.